Informality and Gender Gaps Going Hand in Hand - Malta, Vivian (IMF Working Papers; Working Paper ;, 2019)
In sub-Saharan Africa women work relatively more in the informal sector than men. Many factors could explain this difference, including women's lower education levels, legal barriers, social norms and demographic characteristics. Cross-country comparisons indicate strong associations between gender gaps and higher female informality. This paper uses microdata from Senegal to assess the probability of a worker being informal, and our main findings are: (i) in urban areas, being a woman increases this probability by 8.5 percent; (ii) education is usually more relevant for women; (iii) having kids reduces men's probability of being informal but increases women's.